Peran kurikulum merdeka: Penanaman karakter tanggung jawab pada peserta didik dalam kurikulum merdeka - Amelia, Novita Dwi - (Maliki Interdisciplinary Journal, 2024)
Nowadays, educators are required to understand one of the newest curriculum systems that replaces the K-13 curriculum, namely the Independent Curriculum. Because the design of the independent curriculum is not followed by all teachers in Indonesia, so here the author wants to describe some of the roles of the independent curriculum for students. One of the roles that must be owned by students is related to the character of the students themselves. Where the independent curriculum must be able to form a commendable character that is owned by a student personally. Therefore, in this journal, we will discuss how an educator can instill responsible character in each student through an independent curriculum.